Anthropometric profile, vertical jump, and throwing velocity in elite female handball players by playing positions - Vila, H.; Manchado, C.; Rodriguez, N.; Abraldes, J. A.; Alcaraz, P. E.; Ferragut, C. (The Journal of Strength and Conditioning Research, 2012)
Women's handball is a sport, which has seen an accelerated development over the last decade. Although anthropometric and physical characteristics have been studied for male sports teams, in women's handball, studies are scarce. The aim of this study was twofold: first, to describe the anthropometric characteristics, throwing velocity, hand grip, and muscular power of the lower limbs in female handball players and second, to identify the possible differences in these parameters in terms of individual playing positions (center, back, wing, pivot, and goalkeeper). A total of 130 elite female Spanish handball players participated in the study (age 25.74 ± 4.84 years; playing experience 14.92 ± 4.88 years). Anthropometric assessment was performed for all the subjects following the International Society for the Advancement of Kinanthropometry protocols. Furthermore, all the subjects performed a vertical jump test (squat jump and countermovement jump). Hand grip and throwing velocity in several situations were also assessed. A 1-way analysis of variance and a Tukey post hoc test were used to study the differences among individual playing positions. Wings were less heavy, shorter, and showed a smaller arm span than did goalkeepers, backs and pivots (p = 0.001). Additionally, pivots were heavier than centers. Backs and pivots exhibited higher muscular mass than did wings. Total players' somatotype was mesomorphy endomorphy (3.89-4.28-2.29). Centers showed higher throwing velocity levels than did wings in 9-m throws from just behind the line, with a goalkeeper. Backs exhibited higher hand-grip values than did wings. Statistical differences have been established between wings and other specific playing positions, especially with pivot and backs. Coaches can use this information to select players for the different specific positions.